SYNTHESIS AND CHARACTERIZATION OF COPPER(II) COMPLEX WITH 2,6-DIACETYLPYRIDINE-BIS(PHENYLHYDRAZONE) - Belošević, Svetlana; Radanović, Mirjana; Rodić, Marko; Leovac, Vukadin (Bulletin of Natural Sciences Research, 2021)
The syntheses, physicochemical and structural properties of the novel Cu(II) complex with 2,6-diacetylpyridine bis(phenylhydrazone) (L), of the formula [CuL2]Br2 are presented. In the reaction of warm MeOH solutions of the ligand, 2,6-diacetylpyridine bis(phenylhydrazone) and CuBr2 in molar ratio 2:1 resulted in formation of black single crystals of the bis(ligand) complex. This is the first Cu(II) complex with this ligand that is characterized by SC-XRD. Two ligand molecules are coordinated in the usual tridentate mode, via nitrogen atoms of the pyridine ring, and two azomethine nitrogen atoms, forming distorted octahedral environments of the metal ion.
Keywords: Metal complex; Hydrazone; 2,6-diacetylpyridine derivative; Structure determination